Mobilizing IPM for sustainable banana production in Africa: Proceedings of a workshop on banana IPM held in Nelspruit, South Africa - 23 - 28 November 1998 - Frison, Emile A.; Gold, Cliford S.; Karamura, E.B.; Sikora, R.A.; International Network for the Improvement of Banana and Plantain (1999)
This 356-page publication is the proceedings of a workshop held in Nelspruit, South Africa in November 1998. Twenty-one valuable communications are included, giving an up-to-date overview on research activities on weevils, nematodes, pathology and farming systems in sub-Saharan Africa. Nine country-case studies are also presented. Working groups' results and recommendations are included. This book will certainly be very useful for all those interested in IPM, especially in Africa.